A model of the configuration process of HR systems within multinational subsidiaries in Indonesia - Neil Semuel Rupidara (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2019)
This article develops an empirical model of the process through which human resource management (henceforth HR) systems within subsidiaries of multinational companies (MNCs) are constructed. It extends current models that had previously been developed. It integrates empirical evidence and analyses that had been published earlier with unpublished materials from the same research project. The empirical research applied different qualitative methods in data collection, which are also described in this article. Complementing a previous conceptual model, this article adds on a micro-empirical model of the process and five propositions.Keywords: Configuration, Empirical Model, HR Systems; Indonesia, Institutional Theory* Department of Management, Faculty of Economics and Business, Universitas Kristen Satya Wacana Jl. Diponegoro 52-60 Salatiga 50711, Indonesia https://doi.org/10.21632/irjbs.12.3.223-241